Application of the New York Convention to International Investment Arbitration Awards: An Analysis from the Perspectives of Indonesia and China - Yuan, Luo Yuan (Indonesia Law Review, 2025)
Since the 21st century, as countries have increasingly engaged in international economic activities, the economic ties between nations and regions have grown progressively closer, and cross-border investments have surged. Consequently, investment disputes, which often accompany these investments, have emerged as a critical issue that cannot be overlooked by host governments and foreign investors. Currently, the predominant method for resolving investment disputes is through international arbitration. Therefore, the enforcement of investment arbitration awards has become a key indicator of the effectiveness of the dispute resolution mechanism. A significant area of concern and research is whether the New York Convention can be applied to investment arbitration awards. As signatories to the Convention, both Indonesia and China recognize and enforce foreign arbitral awards. This paper analyzes whether foreign arbitral awards encompass investment arbitral awards by examining the content of the Convention, its savings clause, and relevant case law, with the aim of further exploring the implications of applying the Convention to investment arbitral awards and how China and Indonesia should address these implications